Dynamics of neurospecific proteins content and their formation in experimental brain injury - S. V. Ziablitsev; Ya. S. Yuzkiv; O. O. Dyadyk (Patologìâ)
The aim of this study was the determination of neurospecific proteins content, mechanisms of their formation and transfer into blood in the experimental craniocerebral trauma of medium-heavy degree.